Ways of being seen: surveillance art and the interpellation of viewing subjects. Issue 4 (4th July 2018) - Monahan, Torin
ABSTRACT: Critical artworks about surveillance introduce compelling possibilities for rethinking the relationship of people to larger systems of control. This paper analyses a number of art projects that strive to render surveillance visible and cultivate a sense of responsibility on the part of viewers or participants. Some of the projects show the human costs of surveillance-facilitated drone violence and urge viewers to take action, others use tactics of defamiliarization to draw critical attention to everyday surveillance that has become mundane, and still others invite participation as a way of producing discomfort and reflexivity on the part of viewers. The potential of such works to engender ideological critique rests in their ability to foster ambiguity and decentre the viewing subject by capitalizing upon multiple, competing forms of interpellation.